ACTION RESEARCH ON USING SHORT STORIES TO BOOST EFL LEARNERS’ PERFORMANCE: A SYSTEMATIC REVIEW - Parlindungan Pardede (Premise: Journal of English Education and Applied Linguistics, 2021)
Various conceptual and empirical research has revealed that short stories are effective learning tools teachers can use to boost English as a foreign language (EFL) learning performances. However, most EFL teachers are still find using short stories in EFL classrooms challenging. To solve the problem, conducting action research on using short stories in EFL teaching seems to be the best option. This study aims at reviewing action research on using short story use to increase EFL students’ learning achievement. Employing four inclusion and three exclusion criteria, 12 action research articles indexed in Google Scholar and published in 2011-2020 were selected. Data were analyzed using the constant comparative method. The results showed that the use of short stories employing the Before-During-After reading strategy, language-based model, and literature as content model managed to attain the intended outcomes in 2 to 3 cycles. This review is ended by highlighting some research gaps for future action research and future review as well.